The translation of sports injury prevention and safety promotion knowledge: insights from key intermediary organisations - Sheree Bekker; Penny Paliadelis; Caroline F. Finch (BMC, 2017)
Abstract Background A recognised research-to-practice gap exists in the health research field of sports injury prevention and safety promotion. There is a need for improved insight into increasing the relevancy, accessibility and legitimacy of injury prevention and safety promotion research knowledge for sport settings. The role of key organisations as intermediaries in the process of health knowledge translation for sports settings remains under-explored, and this paper aims to determine, and describe, the processes of knowledge translation undertaken by a set of key organisations in developing and distributing injury prevention and safety promotion resources. Methods The National Guidance for Australian Football Partnerships and Safety (NoGAPS) project provided the context for this study. Representatives from five key NoGAPS organisations participated in individual face-to-face interviews about organisational processes of knowledge translation. A qualitative descriptive methodology was used to analyse participants' descriptions of knowledge translation activities undertaken at their respective organisations. Results Several themes emerged around health knowledge translation processes and considerations, including (1) identifying a need for knowledge translation, (2) developing and disseminating resources, and (3) barriers and enablers to knowledge translation. Conclusions This study provides insight into the processes that key organisations employ when developing and disseminating injury prevention and safety promotion resources within sport settings. The relevancy, accessibility and legitimacy of health research knowledge is foregrounded, with a view to increasing the influence of research on the development of health-related resources suitable for community sport settings.